2002
DOI: 10.1002/aic.690480425
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic MRI visualization of two‐phase flow in a ceramic monolith

Abstract: Regular and irregular catalyst packings are extensively used in the chemical industry for promoting mass transfer and chemical reaction between gas and liquid. Traditionally, randomly packed beds of catalyst particles operating in co-current downflow operation, often termed trickle-bed reactors, have been used because of the high mass-transfer rates achievable. More recently, structured supports are increasingly considered for use because of the potential improvements they offer with respect to, for example, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 15 publications
1
42
0
1
Order By: Relevance
“…De TezanosPinto et al [10] have previously revealed that the liquid flow plays an important role in forcing the bubbles to enter the channels. Dynamic visualization by MRI technique also suggests that the proposed system allows achieving good distribution of gas-liquid flow in the monolith channels [16]. It is important since our work was focusing on obtaining a simple monolith reactor with good gas-liquid distribution.…”
Section: Flow Characteristics In M-dbc Reactormentioning
confidence: 98%
See 1 more Smart Citation
“…De TezanosPinto et al [10] have previously revealed that the liquid flow plays an important role in forcing the bubbles to enter the channels. Dynamic visualization by MRI technique also suggests that the proposed system allows achieving good distribution of gas-liquid flow in the monolith channels [16]. It is important since our work was focusing on obtaining a simple monolith reactor with good gas-liquid distribution.…”
Section: Flow Characteristics In M-dbc Reactormentioning
confidence: 98%
“…Therefore, it is believed that the bubbles entered the monolith channels separated from each other by liquid plugs then creating a segmented gas-liquid flow or Taylor flow inside the channels. This phenomenon was revealed by means of visualization of gas-liquid flow in the same reactor setup (air-water system) using magnetic resonance imaging (MRI) technique [16]. Observation of flow revealed the development of a stable gas-liquid dispersion above the monolith, and the dispersion level was easily controlled to introduce gas-liquid flow that allowed the establishment of Taylor flow inside the monolith channels.…”
Section: Flow Characteristics In M-dbc Reactormentioning
confidence: 99%
“…In technical multichannel applications, however, uniform Taylor flow is hardly achieved, because the bubble generation often leads to a distribution of bubble sizes. 13 For a better understanding of the basic hydrodynamic phenomena, experiments on Taylor flow are often performed in visually accessible single channels. Thulasidas et al…”
Section: Introductionmentioning
confidence: 99%
“…Monolithreaktoren haben das Potenzial, die herkömmlichen Dreiphasenreaktoren aufgrund einer besseren Leistungscharakteristik, einer reduzierten Reaktorgröûe und einer erhöhten Sicherheit bei mindestens gleicher Produktivität zu verdrängen [6] [17].…”
Section: Introductionunclassified